Have we learned anything from the 10th most devastating pandemics over the past 3000 years? - Dragos Stefanescu, Cristian (2021)
When I received the invitation to write an editorial about the Romanian perspective on the SARS CoV 2 pandemics, I instantly knew that George Santayana’s quote: “Those who forget the past are condemned to repeat it” would be most apt to describe the Pan-European approach against this global epidemiological crisis.